2016
DOI: 10.5028/jatm.v8i4.599
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cycle Performance Evaluation and Dynamic Response Simulation

Abstract: Power plants operating in combined cycle present higher thermal efficiency (over 60%) and increased power generation when compared to traditional simple cycles, such as gas or steam turbines operating alone. Considering that the power plant evaluated in this paper is already operational, a further development concerning to the power plant control system is required in order to evaluate disturbances and frequency variations, generated by the electrical grid during normal operation, as the loads applied to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Since the power plant is composed of two units (simple and combined), the obtained efficiency was compared to the target value of 49%. This value is the average between the approximate thermal efficiency of simple cycle gas power plants which is in the range of 35–42% 30 , and that average value for CCGTs which is 60% 31 .
Figure 6 The thermal efficiency of the TPP throughout (2010–2017).
…”
Section: Resultsmentioning
confidence: 99%
“…Since the power plant is composed of two units (simple and combined), the obtained efficiency was compared to the target value of 49%. This value is the average between the approximate thermal efficiency of simple cycle gas power plants which is in the range of 35–42% 30 , and that average value for CCGTs which is 60% 31 .
Figure 6 The thermal efficiency of the TPP throughout (2010–2017).
…”
Section: Resultsmentioning
confidence: 99%
“…This work focuses on the dynamic modeling of gas turbines running on LCV gaseous fuels. Several research efforts [22][23][24][25] involving LCV fuel-based power plants can be found in the literature. To the best of the authors' knowledge however, none of these studies details the particularities addressed in this work.…”
Section: Introductionmentioning
confidence: 99%